Model of individualized learning program implementation for inclusive early childhood education - Asti Eka Wijayanti; Iis Siti Aisyah; Agus Tinus (Research and Development in Education (RaDEn), 2025)
This study develops a contextualized model for implementing the Individualized Learning Program (ILP) in inclusive early childhood education. The study was conducted in an inclusive early childhood education institution in Malang, East Java, Indonesia. Using a qualitative descriptive case-study design with embedded descriptive quantification, data were collected through semi-structured interviews, classroom observations, and document analysis. Participants included 12 classroom teachers, 1 special-education companion teacher (GPK), the school principal, and 4 parents of children with special educational needs (SEN). Data collection was conducted in March 2025 and was corroborated by institutional ILP documents and communication logs from the same program cycle. Thematic analysis generated a three-phase ILP implementation cycle—planning, implementation, and evaluation—supported by collaborative practices among teachers, parents, and administrators. To resolve the design–results consistency, quantitative information reported in the Results (percentages/means) is treated as descriptive summaries extracted from school records, checklists, and logs to complement qualitative themes rather than as inferential outcomes. The findings indicate that effective ILP implementation depends on three interrelated dimensions: (1) Institutional Support, (2) Adaptive Learning Design, and (3) Parental Partnership, while key constraints include limited trained staff and facility readiness. The resulting ILP Implementation Model offers an operationalizable, evidence-based framework for strengthening inclusive practices and aligning early childhood services with equitable, quality education goals.